A Bacillus and Lysinibacillus sp. bio-augmented Festuca arundinacea phytoremediation system for the rapid decontamination of chromium influenced soil. (November 2021) - Peng, He; Liang, Ke; Luo, Huanyan; Huang, Huayan; Luo, Shihua; Zhang, AKang; Xu, Heng; Xu, Fei
Abstract: Phytoremediation as an efficient and eco-friendly soil detoxification method has received widespread attention. In this study, two newly screened Chromium (Cr) reducing strains ( Bacillus sp. AK-1 and Lysinibacillus sp. AK-5) were used to remediate Cr contaminated soil in conjunction with the application of hyperaccumulator tall fescue (Festuca arundinacea), thus establishing a soil Cr decontamination system. In this system, soil urease and dehydrogenase activities were increased, the malondialdehyde (MDA) contents in leaves of tall fescue were significantly decreased, while glutathione (GSH) contents increased. In terms of Cr fractions, the proportion of acetic acid extractable Cr decreased by 12.82–20.00% in treatment groups, respectively, compared with CK, while residual Cr increased by 9.41–22.37%. Moreover, biomass, root length and shoot length of tall fescue in treatment groups increased by 80.77–139.74%, 60.85–68.04%, 7.06–27.10%, respectively. In addition, the root system of tall fescue accumulated 303.887–372.167 mg kg −1 of Cr, and the aboveground part accumulated 16.289–19.289 mg kg −1 of Cr. Therefore, the application of strains AK-1 and AK-5 reduced the toxicity of Cr to plants and greatly increased plant accumulation potential, which indicated that AK-1 and AK-5 could improve removal efficiency of phytoremediation in Cr contaminated soil by reducing its bio-toxicity and promoting growth of tall fescue growth. Graphical abstract: Image 1 Highlights: Two newly  Bacillus  sp. AK-1 and  Lysinibacillus  sp. AK-5 isolated and identified. AK-1 and AK-5 achieved 100% and 95.7% Cr reduction rate within 24 h. The reduction ability of the strain was affected by pH and initial concentration. AK-1 and AK-5 obviously reduced Cr translocation factor.